The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1590/s0034-89101983000400003
|View full text |Cite
|
Sign up to set email alerts
|

Coeficiente de mortalidade materna segundo tipo de óbito, grupo etário, paridade, local de residência e tipo de parto: obituário hospitalar, 1975 a 1979. Florianópolis, SC (Brasil)

Abstract: A partir de informações existentes e registradas em Maternidades e Hospitais Gerais de Florianópolis, SC (Brasil) e na Secretaria de Saúde de Santa Catarina, realizou-se estudo das mortes maternas hospitalares numa série histórica de cinco anos (1975 a 1979). Totalizou o levantamento 44 óbitos (dos quais, 65,9% não eram residentes em Florianópolis) e 43.380 nascidos vivos, e com estes dados foram calculados coeficientes de mortalidade materna específicos para tipo de óbito, grupo etário, paridade, local de res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The values obtained did not have uniform variation of increase or decrease, there may not be a trend exhibited (6) . In the series of this study, MMRH was 5.73 maternal deaths from hemorrhage for every 100,000 live births, showing that the risk for death that a pregnant woman had from hemorrhage was five times higher than from other causes.…”
Section: Data Presented Inmentioning
confidence: 75%
See 2 more Smart Citations
“…The values obtained did not have uniform variation of increase or decrease, there may not be a trend exhibited (6) . In the series of this study, MMRH was 5.73 maternal deaths from hemorrhage for every 100,000 live births, showing that the risk for death that a pregnant woman had from hemorrhage was five times higher than from other causes.…”
Section: Data Presented Inmentioning
confidence: 75%
“…Studies about maternal death related to hemorrhage confirmed that MMR was an important indicator for assessing the event and the quality of maternal-infant care services (6,8) .…”
Section: Data Presented Inmentioning
confidence: 99%
See 1 more Smart Citation